Effect of weighted rope jumping training performed by repetition method on the heart rate, anaerobic power, agility and reaction time of basketball players - Orhan, Serdar (My University, 2013)
Total 40 male basketball players, who are competing in the level of junior teams and playing basketball for at least 3 years and whose ages varied between 16 and 19, have participated in this research that is made to examine effects of weighted rope jumping training performed by repetition method on the heart rate, anaerobic power, agility and reaction time of basketball players. Basketball players were separated into two groups randomly being experimental (n=20) and control (n=20) groups. After preparatory rope training for 1 week, training program including weighted rope jumping training by repetition method for 3 days in a week and for 8 weeks was implemented by the experimental group together with the technical training. For the control group, only technical training was applied for three days in a week over the course of 8 weeks. Age, basketball age, height, body weight, resting heart rate, heart rate immediately after the rope training, anaerobic peak and average power, hexagon agility test and right and left hand visual and auditory reaction times of experimental and control groups were measured. Statistical analyses of data obtained were realized in package program in the significance level of 0.05 by means of Paired Simple T-Test for data having normal distribution, and by Wilcoxon and Mann-Whitney U tests in dependent and independent groups for data that do not have a normal distribution. As a consequence, it can be stated that jumping training performed with weighted rope and by explosive tempo and repetition method has influenced the heart rate and anaerobic characteristics positively, and agility and reaction time negatively.
Keywords: Anaerobic; Basketball; Reaction; Rope training; Weighted rope